Karakterisasi Geopolimer Semen Berbasis Terak Feronikel dari Antam Pomala dengan FTIR - Saddam Husin (PKimia FKIP Universitas Halu Oleo, 2021)
Portland cement production produces 1 tonne of CO for every tonne of cement produced. The increasing release of CO2 can cause an increase in the greenhouse effect and environmental damage. Slag, which is a residual material from the smelting of ferrous and non-ferrous minerals in a blast furnace, has the main composition of silica (SiO) and lime (CaO) which can be used as a substitute for conventional cement as a cement geopolymer. Geopolymers are obtained through geopolymerization reactions. Geopolymerization involves a chemical reaction between a solid aluminosilicate material and an alkaline solution. In this study, geopolymer cement was obtained by reacting a mixture of ferronickel slag (Fe-Ni) with various particle sizes of 106, 90, 75 and 63 m mixed with an alkaline solution (NaOH 7 molar and Na2SiO3 with a ratio of Na2SiO3/NaOH = 2.5). The mixture was molded into cubes with dimensions of 50x50x50 mm3 and allowed to stand for 2 days and then in the oven (80oC, 24 hours). Furthermore, the characterization and testing of the physicalmechanical properties of the geopolymer was carried out. Based on the results of the study the content of oxide compounds in the form of SiO (43.07%), and Al2O3 (9.13%). The FTIR spectra show SiO4 bending vibrations (500-620 cm) and SiO4 stretching (830-1010 cm) where an increase in absorbance at a wavelength of 868 cm indicates the formation of geopolymers, the formation of a new absorption peak of 1419 cm in the form of CO3 2- asymmetry.